Calculation of Temperature Fields in Multilayer Plates and Shells with Distributed Heat Sources (MCIT: Proceedings of International scientific and practical conference, 2019)
The aircraft multilayer glazing is considered as arectangular multilayer plate made up of isotropic layers withconstant thickness. The temperature on the side surface of theplate is zero. Convective heat transfer occurs on outer surfaces ofthe plate; on layers' interfaces film heat sources are arranged.The heat conduction equation for an arbitrary plate layer isreduced to the functional equation. A solution of the functionalequation we search in the form of three space functions product.We get the system of ordinary differential equations. Seriesexpansion factors are determined from a system of linearalgebraic equations. A transform of the required function isfound by the second expansion theorem, and the problemsolution has the form of double trigonometrical series.The comparative analysis of the results is carried out with theresults of other method. The method offered can be used fordesigning a safe multilayer glazing under operational andemergency thermal and force loading in different vehicles.
Keywords: safe multilayer glazing, nonstationary thermal conduction, film heat source